Hubungan Karakteristik Pasien dengan Tingkat Kepatuhan Penggunaan Obat Antihipertensi pada Pasien Hipertensi di Puskesmas Gajahan Surakarta - Annisya, Difa Suci; Ovikariani, O; Murtisiwi, Lusia (Indonesian Journal on Medical Science, 2024)
Hypertension is a chronic disease with an increase in arterial blood pressure that cannot be cured so it requires long-term medical therapy, so that long-term medical therapy will affect the fulfillment of many medications. Previous research results showed that less than 50% of patients were non-compliant in taking medication. The results of previous research show that there are factors characteristic of respondents such as age, gender, education level, employment status, comorbidities, and medical therapy. The aim of the research was to determine the characteristics of respondents, the level of respondent compliance and analyze the relationship between characteristics and the level of respondent compliance at the Gajahan Surakarta Community Health Center. This research is a Cross Sectional Study and uses the MARS-5 questionnaire. The number of respondents was 176 selected using purposive sampling. The validity test obtained valid and reliable results, namely the coefficient value for each statement was >0.463 and the Cronbach's Alpha value was 0.704>0.70. The characteristics of respondents were based on age, the highest was 40-60 years, gender was female, educational level, the highest was low education, unemployed employment status, comorbidities with comorbidities and a lot of medical therapy, namely ? 2 drug therapy. The results of the satisfaction level of respondents obtained a high level of satisfaction (51.1%) and low satisfaction (48.9%). The research results show that there is a relationship between the age of the respondent and the level of compliance with a p-value of 0.022 <0.05.